Front Cover: The Synthesis and Optoelectronic Applications for Tellurophene‐Based Small Molecules and Polymers (ChemPhysChem 20/2019). Issue 20 (11th October 2019) - Wu, Xiaoxi; Lv, Lei; Hu, Lifang; Shi, Qinqin; Peng, Aidong; Huang, Hui
Abstract : The Front Cover shows an artistic illustration of tellurophene‐based small molecules. Recent advances in the synthesis and applications of such molecules and polymers based on them are reviewed, including a discussion on the challenges and future of tellurophene‐based materials. More information can be found in the Minireview by X. Wu et al. onpage 2600 in Issue 20, 2019 (DOI:10.1002/cphc.201900386 ).